MODERN ASPECTS OF THE DIAGNOSIS OF SEVERE COMBINED TRAUMA USING COMPUTED TOMOGRAPHY - I. E. Popova; L. T. Khamidova; R. S. Muslimov; T. G. Barmina; S. A. Badigov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. The variety of options for combining injuries and disorders occurring in the body with a combined injury, the need for rapid decision-making on treatment require rapid diagnosis of the entire volume of injuries and determining the severity of the injury, but there is still no single protocol for examining such victims.The aim of the work was to present a modern CT study protocol for patients with concomitant trauma. Materials and methods. The results of computed tomography of 30 patients with severe concomitant trauma were analyzed. All the victims were  admitted in the first hours after the injury. Men were 30 (67 %), women – 10  (33 %), the average age was 41.3 ± 7.6 (22–79) years. Traditional multiphase full-body MSCT was performed in 20 patients, in 10 patients a special  protocol was used for the study of the "whole body" by the method of  divided bolus. The results of the study. Craniocerebral injuries were detected in 15 (50 %), spinal injuries – in 7 (23.3 %). Simultaneous injuries to the chest and abdomen were detected in 19 (63.3 %) of the victims. When subjectively evaluated, the quality of the images obtained using the full-body MSCT  protocol with bolus separation and the standard multiphase protocol for the diagnosis of traumatic injuries was equivalent. The average radiation load per patient with traditional multiphase full-body MSCT is 66 % higher than  with the split-bolus protocol. Conclusions. Full-body MSCT using a split bolus is a modern technique that fully meets the diagnostic conditions for severe combined trauma and, with a decrease in the radiation dose, allows you to determine all possible injuries in the victim in a single study.